2012
DOI: 10.1039/c1pp05242j
|View full text |Cite
|
Sign up to set email alerts
|

Caged glucosamine-6-phosphate for the light-control of riboswitch activity

Abstract: We have synthesized a light-activatable ("caged") derivative of glucosamine-6-phosphate (GlcN6P), which only upon irradiation becomes a cofactor for the glmS riboswitch. This glmS riboswitch maintains its activity when embedded in the 3'-untranslated region of eukaryotic mRNA molecules and caged GlcN6P reduces the amount of translated EGFP upon irradiation with light in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…For example, Wulffen et al reported a photocaged derivative of glucosamine-6-phosphate which functions as the natural ligand for the glmS riboswitch in vitro. 8 Walsh et al used a photocaged theophylline 9 to optically activate gene expression via a synthetic riboswitch in Escherichia coli. 10 An analogous attempt to regulate gene expression in mammalian cells was reported by Young et al, who synthesized and used photocaged toyocamycin, 11 but the mechanism of gene expression activation by toyocamycin was attributed to nonspecific incorporation of the nucleic acid analog into cellular RNAs, 12 not based on aptamerligand interaction.…”
mentioning
confidence: 99%
“…For example, Wulffen et al reported a photocaged derivative of glucosamine-6-phosphate which functions as the natural ligand for the glmS riboswitch in vitro. 8 Walsh et al used a photocaged theophylline 9 to optically activate gene expression via a synthetic riboswitch in Escherichia coli. 10 An analogous attempt to regulate gene expression in mammalian cells was reported by Young et al, who synthesized and used photocaged toyocamycin, 11 but the mechanism of gene expression activation by toyocamycin was attributed to nonspecific incorporation of the nucleic acid analog into cellular RNAs, 12 not based on aptamerligand interaction.…”
mentioning
confidence: 99%
“…For example, photocaged IPTG ( 19 ) was used successfully to homogeneously express YFP by a LacY − /LacI − bacterial E. coli Turner(DE3) [28]. Comparably, caged carbamate GlcN6P ( 20 ) was successfully used for the temporal activation of glmS responsible for the regulation of gene expression and thus the down-regulation of EGFP in EGFP expressing HeLa cells [29]. …”
Section: Non-natural Sugars For Temporal Control Of Cell Machinery Acmentioning
confidence: 99%
“…[72,73] Nach einem ähnlichen Ansatz benutzten Koh et al NV-geschütztes Doxycyclin, um Ephrin A5 in NIH-3T3-Zellen zu exprimieren und damit die Anordnung von Zellen in einer lebenden Zellmonoschicht zu steuern (Abbildung 3). [76] Die Anwendung dieses Ansatzes beschränkt sich derzeit auf zellfreie Systeme, da der hochpolare Cofaktor nicht die Lipid-Doppelschicht von eukaryotischen Zellen passieren kann. Ribozyme sind z.…”
Section: Angewandte Aufsätzeunclassified
“…In unserem eigenen Beitrag nutzten wir das Ribozym glmS zur Steuerung der GFP-Translation in Retikulozyten-Lysaten und konnten mit einer NPP-geschützten Version des Ribozym-Cofaktors Glucosamin-6-phosphat Lichtregulation der GFP-Produktion erreichen. [76] Die Anwendung dieses Ansatzes beschränkt sich derzeit auf zellfreie Systeme, da der hochpolare Cofaktor nicht die Lipid-Doppelschicht von eukaryotischen Zellen passieren kann.…”
Section: Angewandte Aufsätzeunclassified